PENERAPAN METODE DISKUSI DENGAN MENGGUNAKAN MEDIA GAMBAR UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VII A SMP 3 TAMBANG - Tity Hastuti; Agus Baskara; Ewa Susanti (Perspektif Pendidikan dan Keguruan, 2014)
The purpose of this research paper is as one of the alternative solutions to problems faced by the parties in improving the quality of learning berkepentigan IPS through the method of discussion with media images. The subject of this research is the students of class VII A junior 3 Mine totaling 35 students. The approach used in this study is classroom action research (PTK), each cycle consisting of planning, implementation, observation, and reflection, research conducted by two cycles, each cycle is 2 meetings with one test. This research was conducted from March to April 2013 were applied to the principal subject of understanding the local economy. The data collection techniques using observation sheet and achievement test, while the techniques of data analysis using descriptive analysis.The results showed that the method of discussion by using media images can improve learning outcomes IPS students of class VII A junior 3 Mine. This method uses a discussion with media images have been implemented as well as possible so as to increase the activity of teachers in the first cycle 18 (quite perfect), to two 23.3 (perfect). Then the student activity was also seen in the first cycle is 62%, an d in the second cycle of 87.1%